EXTRACTION OF DAMMAR RESIN (Agathis dammara) USING MICROWAVE-ASSISTED HYDRO-DISTILLATION (MAHD) - A'yuni, Dewi Qurrota; Alhanif, Misbahudin; Hasna, Afifah; Halizah, Nurul; Damayanti, Damayanti; Auriyani, Wika Atro; Fahni, Yunita; Sanjaya, Andri; Mustafa, Mustafa; Kodarif, Abdul Rozak; Rahmiyati, Lutfia; Turnip, Nina Juliana Roberta; Safitra, Edwin Rizki; Saputri, Desi Riana (JURNAL INTEGRASI PROSES, 2025)
Dammar resin (Agathis dammara) is a mixture of various organic polymers in a solid or semi-solid form that can be utilised as an essential oil source. This study extracted the essential oil from dammar resin using microwave-assisted hydro-distillation (MAHD), considering its ability to extract the product in a short period with only a small amount of solvent. This study investigates the effect of solvent and extraction time on the yield of dammar resin extract. Results showed that the highest yields are 27.500, 22.902, and 15.392% for distilled water, a 1:1 v/v mixture of ethyl acetate and distilled water, and a 1:1 v/v mixture of hexane and distilled water as solvents, respectively. The optimum extraction time was different for different solvents, in the 60–90 minute range. Based on the gas chromatography-mass spectrometry (GC-MS) analysis, the dammar resin extract contains several groups of components, including alcohol and sesquiterpene groups. The alcohol group was higher after extraction using an ethyl acetate and distilled water mixture, especially 2-Butoxyethanol, with a yield of 39.706%. Meanwhile, a mixture of hexane and distilled water increased the sesquiterpene compounds in products such as Germacrene D, yielding 19.975%.